PREVALENCE, ANTIBIOGRAM AND BIOFILM PRODUCTION OF LISTERIA MONOCYTOGENES FROM FAECES AND FOETUSES of slaughtered pregnant cows: environmental AND PUBLIC HEALTH IMPLICATIONS (2021)
The indiscriminate slaughter of pregnant animals which characterizes most developing countries poses increasing environmental and public health risks from Listeria monocytogenes infections which are endemic in such settings. The available reports show increasing trends of Listeria monocytogenes infections in both humans and animals in Nigeria. This study examined the prevalence, antibiogram and biofilm production of L. monocytogenes from faeces and foetuses of slaughtered pregnant cows in Ibadan Central Abattoir, Nigeria. Faecal (n = 118) and foetal (n = 118) swabs were cultured and isolates tested for antibiotic susceptibility by Kirby-Bauer assay, while biofilm production was quantified following the standard procedures. The data were analysed using the Chi Square and Student’s t-test at P < 0.05. Listeria monocytogenes were isolated from five (4.2 %) and three (2.5 %) faeces and foetus swabs, respectively, without significant association with sample type (P = 0.50). The isolates were resistant to all the antibiotics tested except gentamicin; with significantly higher production of biofilm by those from foetal samples (P = 0.012). The detection of widespread antibiotic- resistant L. monocytogenes from faeces and fetuses has important environmental and public health implications, given the risk of contamination through faecal shedding and foetal handling. The biofilm production by the pathogen connotes its ability to persist in the environment, suggestive of the challenging effects to its control. Campaigns against indiscriminate slaughter of pregnant animals, and proper hygiene are advocated to ultimately safeguard human and animal health.